Comparative analysis of blood whole transcriptome profiles in Yili horses pre- and post-5000-meter racing - Su, Yi; Ren, Wanlu; Ma, Shikun; Meng, Jun; Yao, Xinkui; Zeng, Yaqi; Li, Zexu; Li, Luling; Wang, Ran; Wang, Jianwen (Frontiers in Genetics, 2025)
This study employed Yili horses participating in a 5000-meter race as a model to investigate exercise-induced gene expression alterations in peripheral blood using whole transcriptome sequencing. Jugular vein blood samples from the three leading horses were collected pre- and immediately post-race, yielding 2,171 differentially expressed mRNAs (2,080 upregulated, 91 downregulated), 4,375 differentially expressed LncRNAs (4,354 upregulated), and 68 differentially expressed circRNAs (64 upregulated). GO/KEGG analyses demonstrated significant enrichment of differential mRNAs in transmembrane transport function and pivotal signaling pathways (cAMP, MAPK, PI3K-Akt). Differential lncRNAs targeted neuro-signaling pathways (e.g., Neuroactive ligand-receptor interaction, Calcium signaling) and developmental regulators (stem cell pluripotency). Source genes of circRNAs were enriched in axon guidance and immune-related T cell receptor signaling. Molecular functions converged on transporter/receptor activity (mRNA/lncRNA) and nucleic acid/GTP binding (circRNA source genes). The protein-protein interaction analysis identified ten central genes within the heat shock protein family, such as HSP90AA1 and HSPA4. Notably, significant upregulation of HCN4, IGF1, PTHR1, and FGF23 indicated their potential roles in modulating cardiac rhythm, promoting tissue repair, and maintaining calcium-phosphorus homeostasis during exercise adaptation. This study provides comprehensive overview of transcriptomic regulatory mechanisms in the blood of Yili horses, offering a molecular framework for advancing understanding of physiological adaptation to exercise and optimizing equine exercise protocols.